2017
DOI: 10.21010/ajtcam.v14i4.13
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effect of Camel Milk as Anti-Diabetic Supplement: Biochemical, Molecular and Immunohistochemical Study

Abstract: Background: Diabetes is a serious disease affects human health. Diabetes in advanced stages is accompanied by general weakness and alteration in fats and carbohydrates metabolism. Recently there are some scientific trends about the usage of camel milk (CM) in the treatment of diabetes and its associated alterations. CM contains vital active particles with insulin like action that cure diabetes and its complications but how these effects occur, still unclear. Materials and Methods: Seventy-five adult male rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 41 publications
4
25
0
Order By: Relevance
“…In studies on rats, camel milk or its extracts have ameliorated biochemical and histochemical disturbances originating from DM induction. [ 12 13 14 15 ] Moreover, it has shown antidiabetic effects in human studies, as found by a systematic review. [ 16 ] Structural studies have suggested that in this kind of milk, insulin may be present in nanoparticles capable of transporting it into the bloodstream.…”
Section: Introductionmentioning
confidence: 98%
“…In studies on rats, camel milk or its extracts have ameliorated biochemical and histochemical disturbances originating from DM induction. [ 12 13 14 15 ] Moreover, it has shown antidiabetic effects in human studies, as found by a systematic review. [ 16 ] Structural studies have suggested that in this kind of milk, insulin may be present in nanoparticles capable of transporting it into the bloodstream.…”
Section: Introductionmentioning
confidence: 98%
“…In some inflammatory diseases, such as hepatitis, allergies, lactose intolerance and liver damage induced by alcohol, the benefits of camel milk can be related to important immunological components such as lysozyme, lactoferrin, lactoperoxidase, etc. Besides this, antibodies of camel milk have specific structures and functions, which may result in therapeutic benefits with the mechanism of immune system regulation in inflammatory diseases (12). A study showed its ability to ameliorate severe food allergies in children in a short time with a long time interval (13).…”
Section: Introductionmentioning
confidence: 99%
“…Camel milk has been used for controlling Diabetes Mellitus (DM) by traditional medicine. Some favorable effects of camel milk are reported in a number of animal and human diabetic populations (7)(8)(9)(10)(11)(12)(13) as follows: terminating biochemical and immunohistochemical alterations after DM induction in albino rats (7), reducing daily insulin doses in type 1 DM patients (8), reducing glycemic indices in type 2 DM patients (9), modifying hyperglycaemia and oxidative damage in animal studies (10), positive effects on incretin hormones, insulin resistance, and inflammatory cytokines (11), and promoting immune functions (12) in experimental DM. Furthermore, a systematic review has documented the beneficial effects of camel milk on DM (13).…”
Section: Introductionmentioning
confidence: 99%